Implikasi Pernikahan Usia Dini Terhadap Keharmonisan Rumah Tangga Studi Pengadilan Agama Maros Kelas 1b - Suharman, Agung; Akil, M.; Abu Baedah, Said Syarifuddin (Media Hukum Indonesia (MHI), 2025)
This study aims to identify the types of problems that arise in households founded through early marriage and to analyze the factors causing divorce in these marriages from the perspective of the Maros Class 1B Religious Court. This study used a qualitative approach with field research methods using interviews, observation, and documentation. The results indicate that early marriage tends to lead to various household problems, such as emotional instability, economic unpreparedness, a lack of understanding of the rights and obligations of husband and wife, and a high potential for conflict and domestic violence. The main factors causing divorce in early marriages include economic factors, lack of education, cultural pressure, premarital pregnancy, and mental and emotional unpreparedness. This study concludes that early marriage has a significant impact on household harmony and has a high potential to lead to divorce. Therefore, thorough understanding and preparation before marriage are necessary, as well as the active involvement of various parties, including families and legal institutions, in preventing the practice of early marriage.